2016
DOI: 10.1213/ane.0000000000001403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Immunological Effects of Volatile Anesthetics: A Review

Abstract: Volatile anesthetics (VAs) have been in clinical use for a very long time. Their mechanism of action is yet to be fully delineated, but multiple ion channels have been reported as targets for VAs (canonical VA targets). It is increasingly recognized that VAs also manifest effects outside the central nervous system, including on immune cells. However, the literature related to how VAs affect the behavior of immune cells is very limited, but it is of interest that some canonical VA targets are reportedly express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 132 publications
(133 reference statements)
1
56
0
Order By: Relevance
“…Whereas in vitro studies have shown acute effects on microglia cytokine expression by isoflurane, no such effects were reported when examining rodent astrocyte or microglial activity at 1, 3, or 7 days after anesthesia without surgery. 1,2,55,56 To our knowledge, there is currently no experimental evidence for a persistent reduction in microglia activity after 3 to 4 days due to administration of anesthetic agents; however, a contribution of anesthesia to the reductions in TSPO observed in the present study cannot be fully excluded. Another caveat in interpreting our results is the possibility that postoperative pain may have an effect on TSPO binding.…”
Section: Annals Of Neurologymentioning
confidence: 53%
“…Whereas in vitro studies have shown acute effects on microglia cytokine expression by isoflurane, no such effects were reported when examining rodent astrocyte or microglial activity at 1, 3, or 7 days after anesthesia without surgery. 1,2,55,56 To our knowledge, there is currently no experimental evidence for a persistent reduction in microglia activity after 3 to 4 days due to administration of anesthetic agents; however, a contribution of anesthesia to the reductions in TSPO observed in the present study cannot be fully excluded. Another caveat in interpreting our results is the possibility that postoperative pain may have an effect on TSPO binding.…”
Section: Annals Of Neurologymentioning
confidence: 53%
“…This result suggested that their swimming defect was not due to defect in flagellin expression. It is a general consensus that anesthetic effect by volatile anesthetics is through their interaction with multiple ion channels [32]. Therefore, we predicted that swimming impairment by isoflurane would derive from its interaction with multiple ion transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Then, Fas DD changes its conformation (2) to bind to FADD (PDB: 3EZQ) (3). Fas-FADD multimers will be more stable than monomer (4) to facilitate procaspace 8 binding (5) that leads to caspase 8 activation (6) followed by caspase-3 activation (7). Red arrows indicate predicated responses by sevoflurane exposure.…”
Section: Discussionmentioning
confidence: 99%